2023
DOI: 10.1097/brs.0000000000004677
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Lumbar Spine Kinematics During Gait May Explain Improvement in Back Pain and Disability in Patients With Hip-Spine Syndrome

Abstract: Study Design. Prospective cohort. Objective. Determine if total hip arthroplasty (THA) changes lumbar spine kinematics during gait in a manner that explains the improvements in back pain seen in patients with hip-spine syndrome. Summary of Background Data. For patients with hip-spine syndrome, improvements in both hip and back pain have been demonstrated after THA; however, the exact mechanism of improvement in back pain remains unknown, as no corresponding changes in lumbar spine static radiographic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Patients included in the present study 1 were meticulously screened for hip and spine pathology and underwent extensive physical exam by both spine and arthroplasty specialists. Ultimately, while patients were seen by a spine surgeon and had spinal pathology, the physical exam and imaging findings suggested that hip pathology was predominant.…”
mentioning
confidence: 99%
“…Patients included in the present study 1 were meticulously screened for hip and spine pathology and underwent extensive physical exam by both spine and arthroplasty specialists. Ultimately, while patients were seen by a spine surgeon and had spinal pathology, the physical exam and imaging findings suggested that hip pathology was predominant.…”
mentioning
confidence: 99%